To seal a wound, caterpillars transform blood from a viscous to a viscoelastic fluid in a few seconds - Aprelev, Pavel; Brasovs, Artis; Bruce, Terri F.; Beard, Charles E.; Adler, Peter H.; Kornev, Konstantin G. (Frontiers in Soft Matter, 2024)
In insects vulnerable to dehydration, the mechanistic reaction of blood after wounding is rapid. It allows insects to minimize blood loss by sealing the wound and forming primary clots that provide scaffolding for the formation of new tissue. Using nano-rheological magnetic rotational spectroscopy with nickel nanorods and extensional rheology, we studied the properties of blood dripping from the wound of caterpillars of the Carolina sphinx moth (Manduca sexta) with a high concentration of blood cells. We discovered that wound sealing followed a two-step scenario. First, in a few seconds, Newtonian lowviscosity blood turns into a non-Newtonian viscoelastic fluid that minimizes blood loss by retracting dripping blood back to the wound. Next, blood cells aggregate, starting from the interfaces and propagating inwardly. We studied these processes using optical phase-contrast and polarized microscopy, X-ray imaging, and modeling. Comparative analyses of the cell-rich and cell-poor blood of different insects revealed common features of blood behavior. These discoveries can help design fast-working thickeners for vertebrate blood, including human blood.